STRUCTURAL AND EARTHQUAKE EVALUATIONS ALONG JAVA SUBDUCTION ZONE, INDONESIA - Adi Patria; Atin Nur Aulia (Indonesian Institute of Sciences, 2020)
Java Subduction is a zone of trench perpendicular convergence of Australian Plate and Southeast Asia in the south of Java. It is characterized by an almost E-W trending trench with an eastward increase of convergence velocity. Three major earthquakes with tsunamis have been caused by deformation along this subduction zone. Although many studies have undertaken to understand the nature of the subduction system, a clear relationship between structures and earthquake activities remains poorly explained. In this study, we used bathymetry, residual bathymetry, and published seismic reflection profiles to evaluate structural and morphological elements, then link the observations to earthquake activity along Java Subduction Zone. Based on seafloor morphology, characteristics of the accretionary wedge and forearc basin varies along the trench in response to the variation of seafloor morphology. Features such as seamounts and ridges which were observed in the oceanic basin may be subducted beneath accretionary wedge and disrupt the morphology of accretionary wedge, forearc basin, and trench. Earthquake activities are generally dominated by normal fault solutions in the trench, which is attributed to plate bending faults while thrust fault solution is observed in the forearc basin area. Thrust fault activities in accretionary wedge are decreased to the east, where there is no thrust fault solution observed in the eastern end of the subduction zone. Few strike-slip focal mechanisms are observed and mainly located within the subducting oceanic plate. Structures and subducting oceanic features may control the earthquake activity where deformation occurred at the edge of these features. The two largest thrust fault earthquakes in 1994 and 2006 are interpreted as a result of deformation along with plate interface on soft or unconsolidated sediment above the incoming plate. The largest normal fault earthquake with a magnitude 8.3 is possibly caused by a crustal scale-fault that breaks the entire oceanic crust.ABSTRAK - Evaluasi struktur dan gempa bumi di sepanjang zona subduksi Jawa, Indonesia. Subduksi Jawa adalah zona konvergensi yang tegak lurus palung antara Lempeng Australia dan Asia Tenggara di selatan Jawa. Hal ini ditandai dengan palung berarah hampir barat–timur dengan peningkatan kecepatan konvergensi ke arah timur. Tiga gempa bumi besar dengan tsunami disebabkan oleh deformasi di sepanjang zona subduksi ini. Meskipun banyak penelitian telah dilakukan untuk memahami sifat sistem subduksi, hubungan antara struktur dan kegiatan gempa bumi masih kurang jelas. Dalam studi ini, kami menggunakan batimetri, batimetri residual, dan profil refleksi seismik untuk mengevaluasi elemen struktur dan morfologi, kemudian menghubungkan pengamatan dengan aktivitas gempa bumi di sepanjang zona subduksi Jawa. Berdasarkan morfologi dasar laut, karakteristik prisma akresi dan cekungan busur muka bervariasi di sepanjang palung sebagai respon terhadap variasi morfologi dasar laut. Fitur seperti seamount dan punggungan yang diamati di cekungan samudera menunjam di bawah prisma akresi dan mengganggu morfologi prisma akresi, cekungan busur muka, dan palung. Aktivitas gempa bumi umumnya didominasi oleh patahan normal di palung, yang dikaitkan dengan patahan tekukan lempeng sedangkan patahan naik diamati di daerah cekungan busur muka. Aktivitas sesar naik di dalam prisma akresi berkurang ke arah timur, di mana tidak ada patahan naik yang teramati di ujung timur zona subduksi. Beberapa mekanisme patahan mendatar diamati dan terutama terletak di dalam lempeng samudera yang menunjam. Struktur dan fitur di kerak samudra yang menunjam dapat mengontrol aktivitas gempa bumi di mana deformasi terjadi di tepian fitur ini. Dua gempa bumi besar dengan sifat patahan naik pada tahun 1994 dan 2006 ditafsirkan sebagai hasil dari deformasi di sepanjang antarmuka lempeng pada sedimen lunak atau tidak terkonsolidasi di atas lempeng yang masuk. Gempa bumi besar dengan sifat sesar normal magnitude 8,3 mungkin disebabkan oleh patahan skala-kerak yang menghancurkan seluruh kerak samudera.